Wyniki oceny efektów finansowych łączenia spółek na podstawie danych księgowych w Polsce - Perepeczo, Agnieszka (The Evidence on Operating Performance in Mergers on the Warsaw Stock Exchange, 2008)
The paper provides evidence on operating performance in merges on the Warsaw Stock Exchange. The research sample has included 13 mergers between 1997 and 2003. The research study has focused on pre-merger period (-3, -1) and post-merger periods (+1, +3) and (+1, +4) according to the merger year t = 0. The operating performance was measured considering the methodology used on developed markets. The operating cash flow return and change model were applied. The achieved results lead to the conclusion that there is no positive change in operating performance after transaction in comparison to pre-merger period. The results are similar to research on developed markets following profit return ratio and they differ from the latest studies of changing in operating cash flow.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 432-440